The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11356-012-0835-y
|View full text |Cite
|
Sign up to set email alerts
|

Blooming of Microcystis aeruginosa in the reservoir of the reclaimed land and discharge of microcystins to Isahaya Bay (Japan)

Abstract: Since a large amount of MCs always suspends in the water in the reservoir and it has been discharged to the bay, suspension-feeding animals are exposed most seriously to the high levels of MCs occurring in these areas. We need to pay attention to the danger of widespread dispersal of MCs and biological concentration of MCs by fish and clam inside and outside the reservoir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…We counted the Microcystis cells in the water samples using a plankton counting chamber (MPC-200, Matsunami Glass, Osaka, Japan) under a microscope. For the determination of MCs, water and sediment samples were pretreated according to methods described by Umehara et al (2012). The concentration of MCs in the pretreated samples were measured by the immunoassay method using a Microcystin Plate Kit (Beacon Analytical Systems Inc., Portland, ME, USA) following the manufacturers recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We counted the Microcystis cells in the water samples using a plankton counting chamber (MPC-200, Matsunami Glass, Osaka, Japan) under a microscope. For the determination of MCs, water and sediment samples were pretreated according to methods described by Umehara et al (2012). The concentration of MCs in the pretreated samples were measured by the immunoassay method using a Microcystin Plate Kit (Beacon Analytical Systems Inc., Portland, ME, USA) following the manufacturers recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Cyanobacteria, including a toxic species, Microcystis aeruginosa (Kütz. ), have bloomed repeatedly in the reservoir in the warm season since the mid-2000s, due to the extremely eutrophic conditions (Migita et al, 2006 Umehara et al, 2012). Water in the reservoir has often been discharged into the bay to maintain the water levels inside the reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increases in lake eutrophication and cyanobacteria blooms have frequently occurred, seriously affecting water environmental safety (Sager 2009;Umehara et al 2012). Therefore, searching for a highly effective, safe, and simple cyanobacteria control method has become a study frontline and hot topic in the field of water environmental protection (Heisler et al 2008;O'Neil et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Without any external interference, the extracellular concentration of algal toxins was very low and negligible during the early culture stage of algal cells and remained at a relatively low level prior to the stable growth stage (Robillot et al 2000), lower than the maximum limit of 1 μg L −1 in drinking water suggested by the World Health Organization (Codd et al 2005;Umehara et al 2012). However, the application of chemical algae-killing reagents causes the death and disruption of algal cells, or the cells being inactive and lysis, leading to a substantial release of intracellular algal toxins (Daly et al 2007;Xiao et al 2010).…”
Section: Extracellular Mcs Release Affected By Artemisinin Sustained-mentioning
confidence: 83%